Seleção indireta de genótipos de tomateiro industrial resistentes ao ácaro rajado - Baier, João Eduardo (2012)
This work aimed to study the levels of resistance to the mite Tetranychus urticae on industrial tomato genotypes pre-selected on the basis of foliar acyl-sugars contents. The tomato breeding has advanced significantly in relation to the resistance to arthropod pests mediated by allelochemicals present on the leaflets surface. Acyl-sugars exuded by glandular trichomes type IV present on accession `LA-716` Solanum lycopersicum are responsible for contributing positively to the tomato breeding, allowing obtaining arthropod pests high levels resistance cultivars. Contrasting plants were selected for the levels of acyl-sugars in the leaves of plants of F2 generations from the interspecific cross between Solanum pennellii `LA-716` (wild accession with high levels of acyl-sugar and pests resistances source) and Solanum lycopersicum `Redenção` (commercial cultivar with low levels of acyl-sugar for industrial processing). Four genotypes were selected with high levels of acyl-sugars in the leaves (RVTA-2010 pl#31, RVTA-2010 pl#75, RVTA-2010 pl#83, RVTA-2010 pl#94) and three genotypes with low levels of acyl-sugars (RVTA-2010 pl#33, RVTA-2010 pl#39, RVTA-2010 pl#73). At the in vivo test for confirmation of the plant selection resistant to the mite T. urticae, genotypes with high levels of acyl-sugars behaved similarly to the resistant parent `LA-716`. The negative correlations between levels of acyl-sugars and distances traveled by the mites on the leaflets surface, confirmed the association between allelochemical high levels and mite resistance. The average degree of dominance (GMD) was estimated to be -0.83, indicating that high levels of acyl-sugars are due the action of a recessive allele with incomplete dominance. The value of 81.85% found for heritability in the broad sense proves that much of the variation between plants in the F2 generation is genetic in heritance. The estimated number of genes was 0.69, so, presumably confirm this is monogenic. The indirect selection method allows effectively the production of industrial tomato plants resistant to the mite T. urticae.